Patients With Newly Diagnosed Hypertension Treated With the Renin Angiotensin Receptor Blocker Azilsartan Medoxomil vs Angiotensin‐Converting Enzyme Inhibitors: The Prospective EARLY Registry. Issue 12 (24th June 2015) - Schmieder, Roland E.; Potthoff, Sebastian A.; Bramlage, Peter; Baumgart, Peter; Mahfoud, Felix; Buhck, Hartmut; Ouarrak, Taoufik; Ehmen, Martina; Senges, Jochen; Gitt, Anselm K.; ,
Abstract : For patients with newly diagnosed hypertension, angiotensin‐converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) are usually the first‐line therapies. There is, however, no real‐life data regarding the relative clinical effectiveness and tolerability of either drug class. The prospective registry, Treatment With Azilsartan Compared to ACE Inhibitors in Antihypertensive Therapy (EARLY), was conducted to evaluate the effectiveness of the ARB azilsartan medoxomil (AZL‐M) vs ACE inhibitors in real‐world patients. Of the 1153 patients with newly diagnosed hypertension who were included in the registry, 789 were prescribed AZL‐M and 364 were prescribed an ACE inhibitor. After multivariate adjustment, AZL‐M was found to provide superior blood pressure reduction and better target blood pressure (<140/90 mm Hg) achievement. The proportion of patients with adverse events was not statistically different between groups. The authors conclude that in newly diagnosed hypertensive patients, AZL‐M provides superior blood pressure control with a similar safety profile compared with ACE inhibitors.